Antiangiogenic alkaloids from plants - Lopes, Flávia Cristine Mascia; Regasini, Luis Octávio [UNESP]; de Magalhães Pinheiro Alçada, Manuel Nuno; Soares, Raquel (Springer Nature, 2013)
Angiogenesis, the formation of new blood vessels from preexisting capillaries, is an important research field. As the understanding of this process increases, this new knowledge will have a significant impact on several angiogenesisdependent diseases. A wide variety of plants are rich in alkaloids, and these compounds have traditionally been of interest due to their pronounced effects on various physiological activities in animals and humans. Nowadays, it is known that many alkaloids obtained from plants exhibit antiangiogenic activity, and these alkaloids may act through different mechanisms to inhibit angiogenesis. Herein, we will discuss the most important alkaloids obtained from plants, focusing especially in their antiangiogenic activity. Because of the great diversity of plants, certainly, there are many antiangiogenic alkaloids that have yet to be discovered.
Keywords: Alkaloids; Angiogenesis; Angiogenesis-dependent diseases; Antiangiogenic activity; Natural products; Plants